2019
DOI: 10.4103/ajns.ajns_238_18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of thrombus density on noninvasive computed tomography neuroimaging for predicting thrombus pathology and patient outcome after mechanical thrombectomy in acute ischemic stroke

Abstract: Background and Purpose: The aim of this study was to investigate the efficacy of thrombus density on noninvasive computed tomography (CT) neuroimaging for predicting thrombus pathology and patient outcome after mechanical thrombectomy in acute ischemic stroke. Materials and Methods: This retrospective chart and imaging review included patients that were treated by mechanical thrombectomy at Siriraj Hospital according to the American Heart Association/American Stroke Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…In terms of imaging findings, the hyperdense artery sign has been associated with RBC-rich thrombi. [1][2][3] Furthermore, one study previously reported that clot permeability, assessed on non-contrast CT and CT angiography, was associated with higher RBC density, 4) while another report showed that permeable thrombi strongly correlated with lower fractions of RBC and more F/P conglomerations. 5) As for treatment outcomes, some studies have shown that high RBC composition was associated with successful recanalization, 6,7) whereas another study reported that a clot with a high number of RBCs had a higher risk of migration, which could lead to worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of imaging findings, the hyperdense artery sign has been associated with RBC-rich thrombi. [1][2][3] Furthermore, one study previously reported that clot permeability, assessed on non-contrast CT and CT angiography, was associated with higher RBC density, 4) while another report showed that permeable thrombi strongly correlated with lower fractions of RBC and more F/P conglomerations. 5) As for treatment outcomes, some studies have shown that high RBC composition was associated with successful recanalization, 6,7) whereas another study reported that a clot with a high number of RBCs had a higher risk of migration, which could lead to worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have measured the areas occupied by red blood cells (RBCs), fibrin/platelets (F/Ps), and white blood cells (WBCs), and examined the relationship between clot composition and clinical characteristics. [1][2][3][4][5][6][7][8][9][10][11][12] However, it is unknown whether the histopathological findings of one cross-section represent the overall composition of the clot. Histopathological composition may differ according to the site of the observed cross-section, even in the same thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography angiography (CTA) of supra-aortic and intracranial vessels is a sensitive and specific tool to detect LVO, and it is now a standard procedure in the diagnostic workflow of AIS. We found 12 articles reporting an association between clot characteristic on CT and histological composition both on retrieved thrombi and on clot analogs [8,16,42,[76][77][78][79][80][81][82][83][84] .…”
Section: Non-contrast Computed Tomography and Computed Tomography Angiographymentioning
confidence: 99%
“…Hyperdense middle cerebral artery sign (HMCAS) is a well-known sign of LVO in AIS on baseline NCCT. Its presence was proved to be related with higher content of RBCs in thrombi [8,42,76,85] , while its absence is related to platelet-rich clots [77,78] .…”
Section: Non-contrast Computed Tomography and Computed Tomography Angiographymentioning
confidence: 99%
See 1 more Smart Citation